Upcycling Guiera Senegalensis waste into biochar for sustainable amoxicillin removal from water - Cheikh Gaye; Jorge Rodríguez-Chueca; Alba Ortíz Fuduo; Modou Fall; Patricia García-Muñoz (Journal of Water Process Engineering, 2025)

Domestic herbivore mobility and herd management at Bronze Age Politiko-Troullia, Cyprus - Suzanne E. Pilaar Birch; Mary Metzger; Elizabeth Ridder; Steven E. Falconer; Patricia L. Fall (Archaeological and Anthropological Sciences, 2025)
This study presents stable isotope analysis of carbon (δ 13 C) and oxygen (δ 18 O) from goat, sheep, and cattle teeth excavated from the Bronze Age village of Politiko- Troullia , Cyprus. The δ 18 O of local water sources and converted δ 18 O drinking water values are used to demonstrate the dietary inputs for goats as compared to those for sheep and cattle. We infer the browsing and grazing behavior of these taxa to reflect different herd management strategies implemented by agropastoral villages during the development of pre-urban Bronze Age society. The δ 13 C and δ 18 O values suggest higher mobility and a more diverse diet for goats in contrast to more constrained ranges and dietary supplementation for sheep and cattle. These conclusions augment our interpretations of animal management at Politiko- Troullia based on previous osteological and isotopic analysis of faunal remains from the site. We contextualize our findings with those of closely comparable faunal and isotopic studies of herd management at contemporaneous Bronze Age settlements.

Assessment of the global toxicity of marine sediments from the Dakar peninsula (Senegal, West Africa) - Amidou Sonko; Dalyal Copin; Patrice Brehmer; Cheikh Diop; Guillaume Constantin De Magny; Mamadou Fall; Yoba Kande; Patricia Moulin; Naby Souleymane Faye; Saliou Faye; Isabelle Linossier; Gaël Le Pennec (Environmental Monitoring and Assessment, 2023)

Vascular plant species of the Kingdom of Tonga by vegetation type, species origin, growth form, and dispersal mechanism - Patricia L. Fall; Taly Dawn Drezner (Ecology, 2020)
The aim of this research is to compile a database of vascular plants found in the Kingdom of Tonga in western Polynesia, a phyto‐geographic subregion of the South Pacific. The Tongan islands are spread over ~600,000 km 2 of the Pacific Ocean between 15–23° S latitude and 173–177° W longitude. The archipelago is comprised of 171 islands with an aggregate land area of about 720 km 2 . Since there is no comprehensive or updated flora for Tonga, we use 143 published sources to compile a database for 1,020 plant species, of which more than 450 are indigenous to these islands. Tonga is noteworthy for its low proportion of endemics, accounting for

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Dispersal ecology of the lowland rain forest in the Vava'u island group, Kingdom of Tonga - Patricia L. Fall; Taly Dawn Drezner; Janet Franklin (New Zealand Journal of Botany, 2007)
We explore the dispersal ecology of the tropical lowland rain forest on the Vava'u island group, Kingdom of Tonga, to understand dispersal adaptations across successional vegetation types and by species origin. We utilise quantitative data on the relative plant abundance (basal area for overstorey and cover for understorey) of forest species from 64 600‐m 2 vegetation plots on 13 islands. Frequencies of species by dispersal mechanisms permit comparisons according to community types, between understorey and overstorey taxa, and between endemic, indigenous, and exotic species (both Polynesian and European introductions). Birds and bats disperse 80% of the plant species in the lowland rain forests of Vava'u; water dispersal (40% of the species) is of secondary importance. Plants introduced by Polynesians comprise 5–10% of the rain forest overstorey; European introductions are common in the early successional forest, principally in the understorey. Over 30% of the indigenous trees in the late successional rain forest are potentially dispersed by rodents, but more likely these introduced (Polynesian and European) rats primarily act as seed predators. Plants in the lowland tropical rain forests of Vava'u are largely dispersed intra‐island by birds and bats. While plants dispersed by epizoochory and human cultivation are encroaching in the early successional stages of the rain forest, perhaps the greater effect on these tropical forests may be seed predation by rodents, especially in late successional rain forest. Since the majority of the indigenous rain forest species are dispersed by native fauna, it is imperative that the extant birds and fruit bats of the Kingdom of Tonga continue to be preserved to maintain the regeneration of the rain forests on these relatively isolated oceanic islands.

Modern pollen precipitation from an elevational transect in central Jordan and its relationship to vegetation - Caroline P. Davies; Patricia L. Fall (Journal of Biogeography, 2001)
Aim To explore the relationship between modern pollen precipitation and vegetation patterns in an arid region of the Middle East. Location Data come from the central Jordan Rift from 1700 m elevation in the highlands to 300 m below sea level in the Dead Sea basin. Methods Modern pollen samples and descriptive vegetation data were collected from twenty‐one locations at 100 m elevational intervals from the highest elevations on the eastern side of the rift valley, where woodlands grow, to the lowest elevation desert on earth, characterized by drought and salt tolerant plants. Pollen percentage data from each vegetation zone are compared descriptively and numerically using cluster and Principal Components Analyses (PCA). Results Three major vegetation zones: woodland, shrub steppe, and desert scrub, are identified by their dominant plant species. The widely spaced tree, Quercus calliprinos Webb, defines the Quercus L. woodland that grows above 1500 m elevation. The shrub steppe can be divided into two subzones found between about 1500 and 900 m elevation: Artemisia herba‐alba Asso shrub steppe and Artemisia L. shrub steppe with Juniperus phoenica L. Desert scrub dominates the lower elevation landscape with Hammada salicornia (Moq.) Iljin the dominant shrub between 900 and 200 m and Haloxylon persicum Bge. found below 200 m elevation. Pollen spectra reflect the elevational vegetation zones. In particular, Quercus L. , Juniperus L. and Tamarix L. pollen are abundant where the trees grow. Highly variable amounts of non‐arboreal pollen taxa – primarily Artemisia L. and Chenopodiaceae Vent. – differentiate shrub steppe from desert scrub vegetation. Cluster and PCA of pollen data support the qualitative vegetation zonation. Main conclusions The main vegetation zones along the Jordan Rift from 1700 to –300 m elevation can be distinguished by their modern pollen precipitation. Open vegetation types, in particular, can be recognized by their pollen spectra. High amounts of Artemisia L. pollen distinguish the moister upper elevations where Artemisia L. steppe grows. In contrast, greater amounts of Chenopodiaceae Vent. pollen characterize the drier, lower elevation deserts.

Plant distribution and dispersal mechanisms at the Hassayampa River Preserve, Arizona, USA - Taly Dawn Drezner; Patricia L. Fall; Juliet C. Stromberg (Global Ecology and Biogeography, 2001)
This study focuses on the relationships between plant dispersal syndromes and plant distributions at the community scale. Species composition and cover are reported from 29 10 × 20‐m vegetation plots along five topographic cross‐sections in the riparian zone of the Hassayampa River Preserve, Arizona. We find that spatial patterns of dispersal guilds vary within the flood plain of this semiarid region river. Our main results are: (1) wind‐dispersed species are fairly evenly distributed at all elevations and distances from the river, whereas cover of animal‐dispersed species increases with elevation above, and at greater distances from, the river; (2) wind‐dispersed species are proportionally more abundant in the pioneer Populus–Salix community, whereas plants in the late‐seral Prosopis community are predominantly animal‐dispersed; (3) most of the species classified as obligate‐wetland and facultative‐wetland are wind‐dispersed, whereas facultative‐upland and obligate‐upland species are mostly animal‐dispersed; and (4) there are significantly fewer wind‐dispersed species in areas of high total vegetation cover. These results may reflect successional patterns resulting from periodic flooding. Low areas close to the river flood more frequently and with greater intensity than areas farther from the river. Many pioneer species that establish in disturbed areas are wind‐dispersed. Over successional time, pioneer species cede to more drought tolerant species that are predominantly animal‐dispersed.

Fire history and composition of the subalpine forest of western Colorado during the Holocene - Patricia Fall (Journal of Biogeography, 1997)
Pollen and plant macrofossils from the Keystone Ironbog are used to document changes in species composition and the dynamics of the subalpine forest in western Colorado over the past 8000 years. Modern pollen spectra (particularly pollen influx), plant macrofossils, observations on modern species composition, and quantified densities and mean basal areas of forest trees are used to interpret the paleoecology of the forest. From 8000 to 2600 years ago the fen was surrounded by a subalpine forest. However, unlike the modern subalpine forest where Abies lasiocarpa (Hooker) Nuttall is slighlty more abundant than Picea engelmannii (Parry) Engelmann, these Holocene forests had a greater dominance of P. engelmannii , perhaps reflecting a summer wet climate like that of the modern southern Rocky Mountains and Colorado Plateau. Mesic conditions promoted a dense understory of Sphagnum moss, forbs, grasses, and shrubs which periodically burned with long (centennial) return‐interval and stand‐replacing fires. Populus tremuloides Michaux was the dominant successional forest tree 8000–6400 and 4400–2600 years ago, with Picea engelmannii and Abies lasiocarpa becoming reestablished within a couple hundred years. A subalpine meadow or grassland covered the fen for about 2000 years between 6400 and 4400 years ago. Over the past 2600 years a stable, non‐successional Pinus contorta (Douglas) spp latifolia (Engelmann) Critchfield forest grew around the fen. This forest stand had a relatively sparse understory. The persistence of Pinus contorta at this elevation (2920 m) probably reflects a shift to drier climatic conditions, perhaps coupled with a change in fire regime to relatively frequent (decadal) surface fires. Following fire Pinus contorta became reestablished at least within 200 years, but the subalpine Picea engelmannii‐Abies lasiocarpa forest never regenerated at this elevation